Line Positions and Intensities of the v1+ v2+ 3v3, v2+ 4v3, and 3v1+ 2v2 bands of ozone; Journal of Molecular Spectroscopy; Vol. 180, № 2 - Mikhailenko S. N. Semen Nikolaevich; Barbe A.; Tyuterev Vl. G.; Regalia A.; Plateaux J. J. (1996, 1996)
Режим доступа: по договору с организацией-держателем ресурса